The conjugacy classes of 3-generator groups of order 16 and some related graphs - Alia Husna Mohd. Noor, 1991-, author 59162 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains) - Universiti Teknologi Malaysia, 2016